Foreign Language Anxiety and Beliefs of EFL Learners at Indonesia - Arief Pramuktiyono; Agus Wardhono (Language Center of Islamic Institute of Uluwiyah (IAI Uluwiyah) Mojokerto Indonesia, 2016)
The present study was aimed to investigate the students of English education Department of University of PGRI Ronggolawe (UNIROW) Tuban. This research fouces on foreign language anxiety beliefs. The population of the present study was 156 students from the fourth semester of English Education Department of UNIROW. The researcher adopted a stratified proportional random sampling technique and 61 students from five classes were selected as participants to fill out all the questionnaires, but after administering the questionnaires only 49 students completely filled out all the questionnaires. The questionnaires used in the present study were Foreign Language Classroom Anxiety Scale (FLCAS) and Beliefs About Language Learning Inventory (BALLI). The findings revealed that there were some factors that contributed to the students’ anxiety in their English classes. Furthremore, the students of English Education Department also validated erroneous beliefs about language learning. Lastly, based on the results of correlation analysis between the FLCAS and the BALLI factors the findings revealed that the students of English Education Department who have greater tendency to perceive themselves as having a good aptitude in language learning tended to be less anxious in the factor of communication apprehension, and likewise, the students who believed English is a difficult language tended to be anxious in the factors of communication apprehension and test anxiety. Thus, the findings of the present study contribute comprehensive picture about students’ foreign language anxiety and students’ beliefs about language learning and it can be used as reference to improve English Education Department at UNIROW Tuban.